Diagnostic value of Interleukin-40 and Interleukin-41 for Diabetic Kidney Disease and Diabetes - Hussain Abdulraheem; Sawsan M. Jabbar AL-Hasnawi; May Mohammed Ali (Karbala Journal of Medicine, 2025)
Background: Diabetic kidney disease (DKD) is a significant microvascular complication of diabetes and a leading cause of end-stage renal disease (ESRD) globally. Inflammatory mediators play a key role in the development of DKD. However, the impact of specific cytokines, such as interleukin-40 (IL-40) and interleukin-41 (IL-41), has not been sufficiently clarified, with limited published data available. This study aimed to evaluate IL-40 and IL-41 levels in individuals with DKD and diabetes mellitus (DM) patients without nephropathy and to investigate their diagnostic capability as biomarkers for distinguishing between these conditions. Methods: This case-control study included 127 participants, divided into three groups: 42 patients with DKD, 43 diabetic patients without kidney disease, and 42 healthy controls. Serum levels of IL-40 and IL-41 were measured using an ELISA assay. Statistical analysis was performed using SPSS, and the diagnostic performance of these markers was evaluated using ROC curve analysis. Results: The study demonstrated a significant decrease in IL-40 and IL-41 concentrations in DKD patients (IL-40: 15.791 ± 8.012 pg/ml, and IL-41: 0.525 ± 0.649 pg/ml) and those with DM (IL-40: 14.114 ± 3.686 pg/ml, and IL-41: 0.641 ± 0.534 pg/ml) compared to the control group (IL-40: 29.859 ± 8.742 pg/ml; IL-41: 3.013 ± 0.983 pg/ml) (p < 0.001). ROC curve analysis showed that IL-41 was more accurate in distinguishing between the control group and DKD patients (98.394%) and between the control group and DM patients (99.567%). Conclusions: The ability of IL-40 and IL-41 cytokines was limited in differentiating between DKD patients and diabetes. Keywords: Interleukin-40, interleukin-41, diabetes kidney disease, diabetes